Novel KCNQ2 and KCNQ3 Mutations in a Large Cohort of Families with Benign Neonatal Epilepsy: First Evidence for an Altered Channel Regulation by Syntaxin‐1A. Issue 3 (13th January 2014) - Soldovieri, Maria Virginia; Boutry‐Kryza, Nadia; Milh, Mathieu; Doummar, Diane; Heron, Benedicte; Bourel, Emilie; Ambrosino, Paolo; Miceli, Francesco; De, Michela; Dorison, Nathalie; Auvin, Stephane; Echenne, Bernard; et al.
<x xml:space="preserve">Abstract</x> Mutations in KCNQ2 and KCNQ3, encoding for Kv7.2 and KV7.3 voltage‐dependent K+ channel subunits, respectively, cause neonatal epilepsies with wide phenotypic heterogeneity. We describe data from 17 patients/families with the diagnosis of benign familial neonatal epilepsy and with a mutation in KCNQ2 (n = 16) or KCNQ3 (n = 1). Electrophysiological studies in mammalian cells revealed that newly found substitutions displayed reduced current densities. In addition, some mutations impair channel regulation by syntaxin‐1‐A, highlighting a novel pathogenic mechanism for KCNQ2‐related epilepsies. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>